Mechanism Research of PZD Inhibiting Lung Cancer Cell Proliferation, Invasion, and Migration based on Network Pharmacology - Feng, Fan; Hu, Ping; Peng, Lei; Chen, Jun; Tao, Xingkui (Current Pharmaceutical Design, 2024)
Background A classic Chinese medicine decoction, Pinellia ternata (Thunb.) Breit.-Zingiber officinale Roscoe (Ban-Xia and Sheng-Jiang in Chinese) decoction (PZD), has shown significant therapeutic effects on lung cancer. Objective This study aimed to explore and elucidate the mechanism of action of PZD on lung cancer using network pharmacology methods. Methods Active compounds were selected according to the ADME parameters recorded in the TCMSP database. Potential pathways related to genes were identified through GO and KEGG analysis. The compound-target network was constructed by using Cytoscape 3.7.1 software, and the core common targets were obtained by protein-protein interaction (PPI) network analysis. Batch molecular docking of small molecule compounds and target proteins was carried out by using the AutoDock Vina program. Different concentrations of PZD water extracts (10, 20, 40, 80, and 160 μg/mL) were used on lung cancer cells. Moreover, MTT and Transwell experiments were conducted to validate the prominent therapeutic effects of PZD on lung cancer cell H1299. Results A total of 381 components in PZD were screened, of which 16 were selected as bioactive compounds. The compound-target network consisting of 16 compounds and 79 common core targets was constructed. MTT experiment showed that the PZD extract could inhibit the cell proliferation of NCI-H1299 cells, and the IC50 was calculated as 97.34 ± 6.14 μg/mL. Transwell and wound-healing experiments showed that the PZD could significantly decrease cell migration and invasion at concentrations of 80 and 160 μg/mL, respectively. The in vitro experiments confirmed that PZD had significant therapeutic effects on lung cancer cells, mainly through the PI3K/AKT signaling pathway. Conclusion PZD could inhibit the cell proliferation, migration, and invasion of NCI-H1299 cells partially through the PI3K/AKT signaling pathway. These findings suggested that PZD might be a potential treatment strategy for lung cancer patients.
Keywords: PI3K/AKT signaling pathway